7(t-3)+5t=4(3t+4)-9

Simple and best practice solution for 7(t-3)+5t=4(3t+4)-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(t-3)+5t=4(3t+4)-9 equation:


Simplifying
7(t + -3) + 5t = 4(3t + 4) + -9

Reorder the terms:
7(-3 + t) + 5t = 4(3t + 4) + -9
(-3 * 7 + t * 7) + 5t = 4(3t + 4) + -9
(-21 + 7t) + 5t = 4(3t + 4) + -9

Combine like terms: 7t + 5t = 12t
-21 + 12t = 4(3t + 4) + -9

Reorder the terms:
-21 + 12t = 4(4 + 3t) + -9
-21 + 12t = (4 * 4 + 3t * 4) + -9
-21 + 12t = (16 + 12t) + -9

Reorder the terms:
-21 + 12t = 16 + -9 + 12t

Combine like terms: 16 + -9 = 7
-21 + 12t = 7 + 12t

Add '-12t' to each side of the equation.
-21 + 12t + -12t = 7 + 12t + -12t

Combine like terms: 12t + -12t = 0
-21 + 0 = 7 + 12t + -12t
-21 = 7 + 12t + -12t

Combine like terms: 12t + -12t = 0
-21 = 7 + 0
-21 = 7

Solving
-21 = 7

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 4(5u+3)-5(2u+1)=27 | | -8=-4+x | | 155-6x=21x+17 | | 12x+22=5x+141 | | 12-9x=30-16x | | 5x-4(5-x)=92 | | 12x+22=5x | | -44-8x=8x+20 | | -40-3x=14-9x | | 125-2x=25x+23 | | 13x+2x+14x=29 | | 5x+12=122-6x | | -2(2s-6)-12=-3(4s+0)-5 | | 8-8x=48-36x | | 2x-5=13-4x | | q=10-2p | | 3(e-4)=24 | | 4x+27=12x-61 | | 3f+5=f+17 | | q=25-p | | 5x+20x-120=0 | | 5xl+20x-120=0 | | 9u-56=24-7u | | 24x+8=14x+28 | | 12x-6=-15x+75 | | 9x-36=3x+36 | | 5x+35=6x-30 | | 27+9x=12+4x | | 12m-21=35-16m | | 34w=306 | | 5+5x=12+6x | | 12-4x+x=22+2x |

Equations solver categories